Challenges associated with road infrastructure in the Galili community, Nyandeni Local Municipality, Eastern Cape Province, South Africa - Kundlwana, Babalo; Asoba, Samson Nambei; Mefi, Nteboheng Patricia (Journal of Ecohumanism, 2025)
Background: Rural road infrastructure is a critical determinant of socio-economic development, influencing access to essential services, mobility, and quality of life. In South Africa, inadequate road infrastructure in rural areas perpetuates poverty and social exclusion, raising concerns about human dignity and sustainability. Within an ecohumanist framework, these infrastructural challenges are not merely technical but relate to broader issues of social justice and environmental stewardship. Aim: The aim of this article is to examine the challenges associated with road infrastructure in the Galili community and to explore the measures adopted by community members to address these challenges. Setting: The study was conducted in the Galili community under the Nyandeni Local Municipality, Eastern Cape Province, South Africa, a predominantly rural area with severe road infrastructure limitations. Methods: A qualitative research design was employed, using semi-structured interviews with residents aged 18 to 65 years. Convenience sampling was applied, and data collection continued until thematic saturation was achieved. Data were analysed thematically, following the six-phase approach. Results: Findings revealed significant infrastructural challenges, including road impassability during rainy seasons, dust-related health risks during dry periods, restricted emergency service access, and limited public transport options. Community members adopted coping measures such as pooling resources for ad hoc repairs, reporting issues to local authorities, and engaging in informal advocacy. However, these measures were temporary and unsustainable due to a lack of technical expertise and institutional support. Conclusion: The study demonstrates that poor rural road infrastructure compromises mobility, access to essential services, and quality of life, contravening the ecohumanist principles of equity and human dignity. While community initiatives show resilience, long-term solutions require systemic interventions integrating participatory governance and climate-resilient designs. Contribution: This article contributes to the ecohumanist discourse by highlighting the lived experiences of rural communities in infrastructural governance, offering insights for policy frameworks that combine sustainability, inclusivity, and community empowerment.